Activity of Zuriat Fruit Extract (Hyphaene thebaica) on The DNA Fragmentation and Spermatozoa Quality of Male Mice (Mus musculus) Given Balinese Arak - Ni Wayan Sukma Antari; Ida Ayu Manik Damayanti (Postgraduate, University of Mataram, 2025)
Alcohol in the body is metabolized into acetaldehyde with the assistance of the enzyme alcohol dehydrogenase (ADH). Acetaldehyde, the metabolic byproduct of alcohol, plays a role in the formation of Reactive Oxygen Species (ROS). The effects of alcohol can lead to damage and death of spermatogenic cells caused by acetaldehyde, which is produced through the breakdown of alcohol by liver cells. Increased ROS levels generated by free radicals in sperm producing tissues may cause damage to the sperm membrane, thereby disrupting its stability and function. High concentrations of ROS may also exert toxic effects on sperm quality and function. This study aimed to examine the activity of Zuriat fruit (Hyphaene thebaica) extract on sperm quality and DNA fragmentation in male mice (Mus musculus) administered Balinese Arak. This research employed an experimental study design using a post-test only control group design. The results show that Zuriat fruit (Hyphaene thebaica) extract at doses of 1 g/kg body weight and 2 g/kg body weight significantly influenced sperm count, motility, viability, morphology, and DNA fragmentation (p < 0,05).